PENGGUNAAN KERTAS ORIGAMI UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI BANGUN DATAR SISWA KELAS III SD - Farulyan, Neska; Rahmawati, Siti; Alfiqri, M.pr; Saputra, Dika; Kharanza, Yoenua; Rohani, Siti; Hopeman, Teofilus Ardian (STKIP Persada Khatulistiwa Sintang, 2024)
The study aims to determine the effectiveness of using origami paper in improving the learning achievement of grade III elementary school students. The research method used is classroom action research (CAR) which is carried out in two cycles. Data collection is carried out through observation sheets and comprehension tests. The results of the study found that although the average academic achievement of students in the